Cangrelor in Older Patients Undergoing Percutaneous Coronary Intervention: Findings From CHAMPION PHOENIX. (August 2017) - Cavender, Matthew A.; Bhatt, Deepak L.; Stone, Gregg W.; Steg, Ph. Gabriel; Gibson, C. Michael; Hamm, Christian W.; Price, Matthew J.; Prats, Jayne; Elkin, Steven; Deliargyris, Efthymios N.; Mahaffey, Kenneth W.; White, Harvey D.; et al.
Abstract : Background—: Older patients treated with percutaneous coronary intervention are at increased risk of periprocedural events. Methods and Results—: CHAMPION (cangrelor versus standard therapy to achieve optimal management of platelet inhibition) PHOENIX randomized 11 145 patients to cangrelor or clopidogrel. We sought to determine the outcomes in the prespecified subgroup of patients ≥75 years old (n=2010; 18%). Cangrelor resulted in directionally consistent effects on the primary end point (death, myocardial infarction, ischemia-driven revascularization, or stent thrombosis) in patients ≥75 years old (odds ratio [OR], 0.71; 95% confidence interval [CI], 0.50–1.02) and in those <75 years old (OR, 0.81; 95% CI, 0.67–0.98; P [interaction]=0.55). Age ≥75 years was an independent predictor of GUSTO (Global Use of Strategies to Open Occluded Coronary Arteries) moderate/severe bleeding (1.0% versus 0.3%; adjusted OR, 2.94; 95% CI, 1.28–6.77; P =0.01) when compared with patients <75 years old. There was no significant difference in GUSTO moderate/severe bleeding with cangrelor versus clopidogrel (1.1% versus 1.0%; OR, 1.07; 95% CI 0.45–2.53) in patients ≥75 years old or in those <75 years old (0.4% versus 0.2%; OR, 2.24; 95% CI, 1.02–4.93; P [interaction]=0.21). For the net composite end point of death, myocardial infarction, ischemia-driven revascularization, or stent thrombosis plus GUSTO moderate/severe bleeding, the OR for cangrelor in those ≥75 years old was 0.75 (6.4% versus 8.3%; 95% CI, 0.54–1.05; P =0.09). The effects were similar in those <75 years old (4.9% versus 5.8%; OR, 0.85; 95% CI, 0.70–1.02; P =0.08; P [interaction]=0.53). Conclusions—: Patients ≥75 years old have an overall ≈3-fold increased odds of moderate/severe bleeding. Cangrelor, when compared with clopidogrel, provides similar efficacy and in patients ≥75 years old as in those <75 years old but does not increase the risk of major bleeding. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01156571. Abstract : Supplemental Digital Content is available in the text.